CORRELATION OF BODY MASS INDEX WITH LEVEL OF PHYSICAL FITNESS DURING THE COVID-19 PANDEMIC (Journal of Physical Education Health and Sport, 2022)
The COVID-19 pandemic has had a negative impact on all sectors, including the education sector. Since the Covid-19 pandemic in Indonesia, all activities have been subject to restrictions. Education is also one of the places that are negatively affected. The policy of learning from home will certainly affect the physical activity of students. When students have low activity, it will affect their body mass index and cardiovascular fitness level. This study aims to determine the correlation between Body Mass Index and cardiovascular fitness levels of Dirgantara Putra Bangsa Vocatinal School students who take part in extracurricular sports during the covid-19 pandemic. This study is an observational study with a cross-sectional design. The sample size is 40 athletes consisting of 20 male students and 20 female students. Cardiovascular fitness level was measured using a 2.4-kilometer run test. The analysis test used the Pearson product-moment test to see the relationship between body mass index and cardiovascular fitness level. The results showed that there was no relationship between body mass index and the level of cardiovascular fitness of Dirgantara Putra Bangsa Vocational School students who took part in extracurricular sports with a significance value of p = 0.882. This study concludes that there is no correlation between body mass index and cardiovascular fitness levels in Dirgantara Putra Bangsa Vocational School students who take part in extracurricular sports during the COVID-19 pandemic